2014
DOI: 10.1186/s12888-014-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Seeking informal and formal help for mental health problems in the community: a secondary analysis from a psychiatric morbidity survey in South London

Abstract: BackgroundOnly 30-35% of people with mental health problems seek help from professionals. Informal help, usually from friends, family and religious leaders, is often sought but is under-researched. This study aimed to contrast patterns of informal and formal help-seeking using data from a community psychiatric morbidity survey (n=1692) (South East London Community Health (SELCOH) Study).MethodsPatterns of help-seeking were analysed by clinical, sociodemographic and socioeconomic indicators. Factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 35 publications
5
46
2
3
Order By: Relevance
“…Previous research from Japan found a significant relationship between depression (as identified by a psychiatric epidemiological survey using the WHO Composite International Diagnostic Interview [27]) and lower presenteeism, but did not identify a significant relationship between presence of depression and absenteeism [9]. It may be that our sample identified a relationship between depression and absenteeism in Japan as our criteria for depression identified individuals with more severe depression, given they had to receive a diagnosis by a medical professional (Brown et al [28]; Bebbington et al [29]) and that there is a high threshold of depression severity which warrants absenteeism in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from Japan found a significant relationship between depression (as identified by a psychiatric epidemiological survey using the WHO Composite International Diagnostic Interview [27]) and lower presenteeism, but did not identify a significant relationship between presence of depression and absenteeism [9]. It may be that our sample identified a relationship between depression and absenteeism in Japan as our criteria for depression identified individuals with more severe depression, given they had to receive a diagnosis by a medical professional (Brown et al [28]; Bebbington et al [29]) and that there is a high threshold of depression severity which warrants absenteeism in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…It might also be due to stigma and the fear of being dismissed from their jobs if their employers find out that they have mental disorders (Honkonen et al 2007), which may have led to low help-seeking in this group. Those who were employed tended to seek informal help, while the unemployed were more likely to seek formal and informal help (Brown et al 2014). The unemployed may have more time (Honkonen et al 2007), have less social support, and lack financial means (Khlat et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Classification of formal and informal bereavement support was derived from similar British [32] and international [33] studies of service use . Self-help was excluded due to problematic categorisation in relation to formal versus informal bereavement support [34].…”
Section: Methodsmentioning
confidence: 99%